2019
DOI: 10.1007/s12350-017-1016-7
|View full text |Cite
|
Sign up to set email alerts
|

A combined static-dynamic single-dose imaging protocol to compare quantitative dynamic SPECT with static conventional SPECT

Abstract: The visually assessed image findings in static and dynamic SPECT are subjective, and may not reflect direct physiologic measures of coronary lesion based on SCA. The CFR measured with dynamic SPECT is fully objective, with better sensitivity and specificity, available only with the data generated from the dynamic SPECT method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…The spatiotemporal 4D reconstruction provides information of the temporal changes of the radiotracer at each spatial point without specifics of the cardiac or respiratory motion. The reconstructed images with MC simulation were compared with the data obtained from the conventional spatiotemporal 4D reconstruction that has been implemented in our earlier publications in patient studies ( 12 , 42 ). In these studies, for a TBR = 8 we binned data over each 3-degree view for a total of 120 views per rotation per detector head.…”
Section: Resultsmentioning
confidence: 99%
“…The spatiotemporal 4D reconstruction provides information of the temporal changes of the radiotracer at each spatial point without specifics of the cardiac or respiratory motion. The reconstructed images with MC simulation were compared with the data obtained from the conventional spatiotemporal 4D reconstruction that has been implemented in our earlier publications in patient studies ( 12 , 42 ). In these studies, for a TBR = 8 we binned data over each 3-degree view for a total of 120 views per rotation per detector head.…”
Section: Resultsmentioning
confidence: 99%
“…With these various cameras, dynamic cardiac SPECT has been performed with various tracers, including: 201 Tl, 99m Tc‐teboroxime, 99m Tc‐sestamibi, and 99m Tc‐tetrofosmin . Recently, some works have shown that dynamic SPECT has promise for measuring flow and coronary flow reserve (CFR) with rotating large field of view gamma cameras . However, in all of these works, it is recognized that because of the slow camera rotation, dynamic data must be reconstructed directly from the projections themselves, that is, performing 4D reconstruction with appropriate corrections for attenuation, partial volume, and scatter …”
Section: Introductionmentioning
confidence: 99%
“…9,13 Recently, some works have shown that dynamic SPECT has promise for measuring flow and coronary flow reserve (CFR) with rotating large field of view gamma cameras. 8,9,[19][20][21] However, in all of these works, it is recognized that because of the slow camera rotation, dynamic data must be reconstructed directly from the projections themselves, that is, performing 4D reconstruction 1,6,7,9,10,[20][21][22] with appropriate corrections for attenuation, partial volume, and scatter. [23][24][25] Algorithms have advanced, 26 including modeling of cardiac motion in dynamic 5D reconstruction, 27,28 modeling of cardiac and respiratory motion in dynamic 6D reconstruction, 29 and directly fitting compartment models.…”
Section: Introductionmentioning
confidence: 99%
“…While dynamic positron emission tomography imaging can differentiate normal perfusion from balanced ischemia by quantifying coronary flow reverse, 34 most of the current SPECT imaging in clinical practice lack the ability to do so (although the newer generation cameras have shown promising results). 35,36 When myocardial stunning occurs during stress testing, there is impaired myocardial contractility and worsening of mechanical synchrony which can be quantified by phase analysis. In the current single-center cross-sectional study from Mexico, Garcia-Cardenas M et al 37 sought to assess the diagnostic performance and added value of LVMD indices by phase analysis of gated SPECT in discriminating patients with 3-vessel CAD from those without CAD.…”
mentioning
confidence: 99%